Analisis Pengelolaan Mata Pelajaran Tahfhizh di SMA PGII 1 Kota Bandung - Annisa Sasilia; Nan Rahminawati; Khambali (UNISBA Press, 2023)
Abstract. The minimum number of hours of pie affects the lack of time to achieve completeness. Additional time is needed to maximize assessment results, especially in cognitive assessment. In the PAI cognitive assessment, students are required to be able to memorize the Qur'anic arguments that support the discussion material during learning. Because of that, additional activities are needed to support the completeness of pies, one of which is the tahfhizh activity. Tahfhizh itself is a program to help students maximize memorizing the verses of the Koran. Due to the problem of lack of learning time in PAI, researchers want to observe how the management of school learning that holds Tahfhizh subject activities, one of which is SMA PGII 1 Bandung. Also supported by the results of observations of student assessments observing that the assessment achieved from Tahfhizh activities at school is categorized as good. Fundamental points in learning management that influence researchers in their research include planning, implementing, and evaluating learning to memorize verses of the Qur'an in the Tahfhizh subject. In this study, researchers used a qualitative descriptive approach using several data collection techniques, namely observational interviews and documentation studies or triangulation. The aim of the research is to show that school process efforts can achieve good assessments from students and also educators. Abstrak. Minimnya jumlah jam pai mempengaruhi kurangnya waktu terhadap capaian ketuntasan. Diperlukannya waktu tambahan untuk memaksimalkan capaian penilaian khususnya pada penilaian kognitif. Pada penilaian kognitif PAI diharuskan peserta didik untuk dapat menghafal dalil-dalil Alquran yang mendukung pada materi pembahasan saat pembelajaran. Sebab itu perlunya kegiatan tambahan untuk mendukung ketuntasan PAI salah satunya adalah kegiatan tahfhizh. Tahfhizh sendiri adalah sebagai program untuk membantu memaksimalkan peserta didik menghafalkan ayat-ayat Alquran. Sebab problem kurangnya waktu pembelajaran pada PAI peneliti ingin mengamati bagaimana pengelolaan pembelajaran sekolah yang mengadakan kegiatan mata pelajaran Tahfhizh salah satunya SMA PGII 1 Bandung. Didukung juga dengan hasil pengamatan penilaian peserta didik mengamati bahwa penilaian yang dicapai dari kegiatan Tahfhizh di sekolah dikategorikan baik. Poin-poin yang mendasar pada pengelolaan pembelajaran yang mempengaruhi peneliti terhadap penelitiannya diantaranya perencanaan, pelaksanaan, dan evaluasi pembelajaran menghafal ayat-ayat Al- Qur’an pada mata pelajaran Tahfhizh. Pada penelitian ini peneliti menggunakan pendekatan kualitatif bersifat deskriptif dengan menggunakan beberapa teknik pengumpulan data yaitu wawancara observasi dan studi dokumentasi atau triangulasi. Tujuan penelitian adalah untuk menunjukkan usaha proses sekolah dapat tercapainya penilaian yang baik dari peserta didik dan juga pendidik.